Technology-Enhanced Language Learning: A Meta-Analysis Study On English Language Teaching Tools - Ira Nurmala; Sugeng Irianto; Sherly Franchisca; Helfany Amsa; Ratna Susanti (Departement of Mathematics Education, 2023)
This meta-analysis study explores the effectiveness of technology-enhanced language learning in the context of English language teaching. Through a comprehensive review of relevant literature, various research studies were examined to gain insights into the impact and potential of technology in language learning. The findings highlight that the use of new technologies positively contributes to learners' language learning skills and enhances their overall proficiency. Mobile learning and ICT tools have been identified as effective resources that facilitate English language learning by providing accessible and efficient learning environments. Additionally, the research indicates that technology-supported language learning is as effective as learning with human teachers, indicating the potential of technology to offer personalized and tailored learning experiences. However, it is crucial to provide teachers with proper training and support to confidently integrate technology into their teaching practices. Educational institutions should offer comprehensive training programs and allocate sufficient time for teachers to enhance their technological skills and confidently utilize educational technologies. These findings underscore the importance of technology in enhancing language learning outcomes and emphasize the need for ongoing support and professional development for teachers in integrating technology into language teaching.